STRATEGI PSK DALAM MENGGUNAKAN MEDIA SOSIAL DI KOTA MANADO - Ratu, Melinda; Mamosey, Welly E.; Mawara, Jetty E. T. (Universitas Sam Ratulangi, 2020)
The development of information technology in Indonesia is fairly fast including the internet turned out to be a great impact on all aspects. With the development of technology that makes many people use this technology to make buy and sell transactions using the Internet. It is not strange considering the growing number of Internet users can be the potential to be entered by businesses anywhere and when they are. Technology, the Internet, and prostitution are three things that are intertwined. Advances in communication and Internet technology allow one to quickly get to the information. Prostitution also does not blind technology and participates in the development of the era so that prostitution becomes increasingly diverse and sophisticated. These two applications are often used by the Michat application and also the Facebook application. In looking for customers using Facebook relies heavily on the Group admins who act as.Â Keywords: Prostitute, Application, Social Media